Global Biogeochemical Cycles - Global Biogeochemical Cycles (Wiley, 2026)
Global Biogeochemical Cycles publishes original research articles on biogeochemical interactions that demonstrate fundamental implications for processes at regional or global scales.
FI 1.2
Q1
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Bioquímica; Sistemas físicos de la Tierra; Clima